Pancreatic tuberculosis: A close mimicker of malignancy - Ankita Soni; Ruchita Tyagi; Pavneet Kaur Selhi; Ajit Sood; Neena Sood (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Soni A, Tyagi R, Selhi PK, Sood A, Sood N. Pancreatic tuberculosis: A close mimicker of malignancy. Turk J Gastroenterol 2019; 30(11): 1001-3.